Search for t t ¯ resonances in highly boosted lepton+jets and fully hadronic final states in proton-proton collisions at √s=13 TeV - Khachatryan, Vardan; Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Asilar, Ece; Md. Ali, Mohd. Adli (American Physical Society, 2017)
A search for the production of heavy resonances decaying into top quarkantiquark pairs is presented. The analysis is performed in the lepton+jets and fully hadronic channels using data collected in proton-proton collisions at √ s = 13 TeV using the CMS detector at the LHC, corresponding to an integrated luminosity of 2.6 fb−1 . The selection is optimized for massive resonances, where the top quarks have large Lorentz boosts. No evidence for resonant t¯t production is found in the data, and upper limits on the production cross section of heavy resonances are set. The exclusion limits for resonances with masses above 2 TeV are significantly improved compared to those of previous analyses at √ s = 8 TeV.